Effects Of Acıd Etchıng Whıch Used Before And After Bleachıng On The Bondıng Strength Of Orthodontıc Brackets - Tancan Uysal; Faruk Ayhan Başçiftçi; Zafer Sarı; Ahmet Büyükerkmen (Galenos Yayinevi, 2002)
Following the bleaching process, there exist some doubts concerning the retention of brackets that are to be bonded during the orthodontic treatment of adult patients who are not plmsed with their denial aesthetics. For this reason, this study aimed to determine the effect upon the shear bond strength of brackets caused by the acid agent applied before and after the bleaching process. Sixty non-carious first premolar teeth which were extracted for orthodontic purposes were used in this study. Samples were divided randomly into 3 groups each consisting of 20 teeth and embedded vertically into acrylic blocks with their crowns being exposed. While the teeth in group 1 were bleached and then exposed to acid agent, the teeth in group 2 were exposed to acid agent and then bleached with the same procedure, and group 3 used as the control group. Afterwards, the brackets of all 3 groups were bonded under standard conditions. After the samples were treated with thermo-cycling procedure, they were placed in the universal testing machine for measurements. Data gained from the results of these procedures were divided by the base area of the brackets in order to calculate the bond strength of the brackets. Furthermore, to determine the fracture site, light microscope was used. Bond strength mean differences among the three groups were tested for statistical significance with an analysis of variance (ANOVA) for fixed effect (p<0.001). Post hoc pairwise mean comparisons were performed with Tukey's HSD procedure. According to the results, while the greatest value of bond strength was found in group 1 samples, the lowest value was found in group 2 samples. As a result, following the bleaching process, re etching of the enamel prior to bonding of the brackets will form the most correct order. It is also recommended that the acid etching be performed in the patients who had their teeth bleached previously.